Kinetic Plasma Turbulence: Recent Insights and Open Questions From 3D3V Simulations - Cerri, Silvio Sergio; Grošelj, Daniel; Franci, Luca (Frontiers in Astronomy and Space Sciences, 2019)
Turbulence and kinetic processes in magnetized space plasmas have been extensively investigated over the past decades via in-situ spacecraft measurements, theoretical models and numerical simulations. In particular, multi-point high-resolution measurements from the Cluster and MMS space missions brought to light an entire new world of processes, taking place at the plasma kinetic scales, and exposed new challenges for their theoretical interpretation. A long-lasting debate concerns the nature of ion and electron scale fluctuations in solar-wind turbulence and their dissipation via collisionless plasma mechanisms. Alongside observations, numerical simulations have always played a central role in providing a test ground for existing theories and models. In this Perspective, we discuss the advances achieved with our 3D3V (reduced and fully) kinetic simulations, as well as the main questions left open (or raised) by these studies. To this end, we combine data from our recent kinetic simulations of both freely decaying and continuously driven fluctuations to assess the similarities and/or differences in the properties of plasma turbulence in the sub-ion range. Finally, we discuss possible future directions in the field and highlight the need to combine different types of numerical and observational approaches to improve the understanding of turbulent space plasmas.